PERGESERAN STRUKTUR PEREKONOMIAN DI PROVINSI SULAWESI UTARA - Marlyanti Tumandung; Paulus A. Pangemanan; Esry O.H. Laoh; Jean F.J. Timban (Universitas Sam Ratulangi, 2014)
ABSTRACTMarlyanti Tumandung. Shifting of Economic Structure in North Sulawesi Province (Underguidance of Paul A. Pangemanan as a Chairman, O. Esry H. Laoh and Jean FJ Timban as Members).The objective of this research is to analyze the economy structural shift in from of the North Sulawesi Province . The study was conducted over three months starting from July 2014 until September 2014 in North Sulawesi Province. The data used in this study was secondary data obtained from the North Sulawesi Province Central Bureau of Statistics. The data used was the Gross Domestic Product ( GDP) at constant prices of 2003-2012 . This analysis uses descriptive .The research result showed that most sectors contributing to the GDP formation in North Sulawesi was the tertiary sector . The contribution of the tertiary sector continued to increase in 2003-2012 period while the primary sector declined .Keyword: Gross Domestic Product ( GDP), primary sector, tertiary sector.